Soft tissue reconstruction using Trevira tube following proximal femur resection and tumorous endoprosthetic replacement - Vasileios Apostolopoulos; Michal Mahdal; Lukáš Pazourek; Pavel Brančík; Marián Kubíček; Ioannis Trikoupis; Panayiotis Gavriil; Petr Boháč; Panayiotis J. Papagelopoulos; Tomáš Tomáš (BMC Musculoskeletal Disorders)
Abstract Background The use of Trevira tubes is beneficial for soft tissue reconstruction following proximal femur resection and endoprosthetic replacement, enhancing joint stability, mobility, and reducing abductor insufficiency. The purpose of the study is to describe the surgical technique and outcomes of soft tissue reconstruction using a Trevira tube following proximal femur resection for malignant bone tumors. Methods This study evaluates the outcomes of 80 patients who underwent proximal femur tumor replacement using dual-mobility hip systems with Trevira tubes in a sarcoma center. Reconstruction revision-free survival rate and failure modes were assessed using the Henderson classification, while functional outcomes were evaluated in 51 patients with a minimum six-month follow-up, assessed using the Harris Hip Score(HHS), Mayo Hip Score(MHS), Musculoskeletal Tumor Society Score(MSTS), Trendelenburg sign, and range of motion. Results The five-year revision-free survival rate was 85.3%. The cumulative incidences at the five-year mark were 6.5% for dislocation and 8.1% for deep infection. Failures occurred predominantly in the early postoperative period (3 ± 2.4 months). Functional outcomes (HHS: 78.71 ± 12.55, MHS: 75.68 ± 13.37 and MSTS: 24.11 ± 3.22) were generally satisfactory, despite the frequent occurrence of abductor muscle insufficiency (37.3%). Statistically significant predictors of survival or functional outcomes were not identified. Nevertheless, trends indicate that patients with pathological fractures and metastases tend to have less favorable outcomes. Conclusion Trevira tube for soft tissue reconstruction following proximal femur resection and endoprosthetic replacement demonstrated promising results, with low failure rates and favorable functional outcomes. While no statistically significant predictors of survival or functional outcomes were identified, trends suggested poorer outcomes in patients with pathological fractures or metastatic bone disease.